DDRE-34. TARGETING RESISTANCE IN MEDULLOBLASTOMA. (25th March 2021) - Chang, Simone; Meiman, Evan; Telang, Sucheta
Abstract: Medulloblastoma is the most commonly diagnosed pediatric brain tumor. Although therapeutic advances have improved survival from this cancer, they result in devastating sequelae and, additionally, have proven inadequate in metastatic disease and recurrence where survival remains <5%. Effective therapies are urgently needed to improve outcomes in medulloblastoma. Medulloblastoma development is driven by dysregulation of normal cerebellar proliferation. Mutations in the sonic hedgehog (Shh) pathway are found in ~30% of these tumors and responsible for their aggressive growth. The poor outcomes in Shh-driven medulloblastoma have prompted the evaluation of Shh-targeting agents in their treatment – with limited success likely attributable in part to the upregulation of alternate survival pathways (e.g. Ras/MAPK and HIF-1α). These alternate mechanisms stimulate glycolysis, in part by increasing the activity of the 6-phosphofructo-2-kinase/fructose-2, 6 bisphosphatases (PFKFB1-4) to produce fructose-2, 6-bisphosphate (F26BP), a potent activator of the rate-limiting glycolytic enzyme, 6-phosphofructo-1-kinase. In recent studies, we have determined that the PFKFB4 enzyme is highly expressed in patient-derived Shh medulloblastomas. We have found that hypoxia, through HIF-1α, strongly induced PFKFB4 expression in Shh-driven medulloblastoma cells and that silencing PFKFB4 suppressed F26BP, glycolysis and proliferation in normoxia and, more markedly, in hypoxia, indicating that PFKFB4 may be required for growth under hypoxia. We found that simultaneously silencing PFKFB4 and Shh pathway effectors significantly reduced cell survival and that co-targeting PFKFB4 (with a novel inhibitor) and Shh effectors synergistically decreased cell viability. In order to simulate Shh antagonist resistance, we have now subjected Shh medulloblastoma cells to prolonged Shh inhibitor exposure and found that these cells exhibit increased proliferation, glycolysis and PFKFB4. Studies are underway to delineate their metabolic alterations. Taken together, our data indicate that targeting PFKFB4 may be a valid therapeutic option in aggressive, treatment-resistant medulloblastoma and strongly support the further examination of PFKFB4 inhibitors in these tumors.